Biomechanics of wrist injuries in sport - Howse, C. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The wrist is mechanically the most complex joint in the body. It comprises of the distal radius and ulna, carpometacarpal joints, and rows of carpal bones. The carpal bones are conventionally assigned into the proximal and distal rows and the scaphoid is reserved the separate status of a bone of bridging the carpal rows on the radial side. The stability of the wrist depends on key ligaments predominately on the volar side and intracapsular ligaments. The ligaments which cross both carpal rows guide the excursion of the proximal row on the distal row, and stabilise the carpus to the distal radius and ulna. The interosseous ligaments of the proximal row provide strong rotation stability.